Capacity Building in Risk Management and Communication for the Prevention, Control, and Eradication of New World Screwworm (Cochliomyia hominivorax–NWS) in Central America - Diaz, Alejandra (2025)
In collaboration with the Inter-American Institute for Cooperation on Agriculture (IICA), USDA Animal and Plant Health Inspection Service (APHIS), International Regional Organization for Agricultural Health (OIRSA), Panama-United States Commission for the Eradication and Prevention of Screwworm (COPEG), Pan American Health Organization / World Health Organization (PAHO/WHO) and the Ministries of Agriculture and Veterinary Services in Central America and Mexico